Screening for Hypertension in the INpatient Environment(SHINE): a protocol for a prospective study of diagnostic accuracy among adult hospital patients. Issue 12 (4th December 2019) - Armitage, Laura C; Mahdi, Adam; Lawson, Beth K; Roman, Cristian; Fanshawe, Thomas; Tarassenko, Lionel; Farmer, Andrew J; Watkinson, Peter J
Abstract : Introduction: A significant percentage of patients admitted to hospital have undiagnosed hypertension. However, present hypertension guidelines in the UK, Europe and USA do not define a blood pressure threshold at which hospital inpatients should be considered at risk of hypertension, outside of the emergency setting. The objective of this study is to identify the optimal in-hospital mean blood pressure threshold, above which patients should receive postdischarge blood pressure assessment in the community. Methods and analysis: Screening for Hypertension in the INpatient Environment is a prospective diagnostic accuracy study. Patients admitted to hospital whose mean average daytime blood pressure after 24 hours or longer meets the study eligibility threshold for mean daytime blood pressure (≥120/70 mm Hg) and who have no prior diagnosis of, or medication for hypertension will be eligible. At 8 weeks postdischarge, recruited participants will wear an ambulatory blood pressure monitor for 24 hours. Mean daytime ambulatory blood pressure will be calculated to assess for the presence or absence of hypertension. Diagnostic performance of in-hospital blood pressure will be assessed by constructing receiver operator characteristic curves from participants' in-hospital mean systolic and mean diastolic blood pressure (index test) versus diagnosis of hypertension determined by mean daytime ambulatory blood pressure (reference test). Ethics and dissemination: Ethical approval has been provided by the National Health Service Health Research Authority South Central—Oxford B Research Ethics Committee (19/SC/0026). Findings will be disseminated through national and international conferences, peer-reviewed journals and social media.